Producer Services and Competitiveness of Manufacturing Exports - Yvonne Wolfmayr (FIW - Research Centre International Economics, 2008)
The paper examines the role of service inputs in shaping the competitiveness of the manufacturing sector. It first estimates an export market share function of 18 manufacturing industries for 16 OECD countries over the period 1995 to 2000. The service linkage variables are derived from Input Output tables. The results point to a positive and highly significant impact of international service linkages in high skilled, technology driven industries that explains about 40 percent of the overall increase in the market share. While there is a clear differential impact across the different types of (consuming) manufacturing industries, the type of service input is not relevant. The second part of the paper estimates the impact of outsourced services as well as in house services on total factor productivity growth in Austrian manufacturing, based on an approach suggested by Feenstra Hanson (1999). The results suggest a positive and significant impact of services outsourcing on TFP growth that is higher in the high skilled intensive manufacturing industries. In contrast to the findings for export market shares, the distinction between the types of service inputs is highly relevant for the results on TFP growth, which stresses the role of knowledge intensive business services (KIBS) as important producers and transmitters of technology, innovations and knowledge (technological and knowledge spillovers). The impact of in house services could not be precisely estimated.
Keywords: 330; Export of Services